An abnormally slow proton transfer reaction in a simple HBO derivative due to ultrafast intramolecular-charge transfer events1. Issue 25 (7th July 2015) - Alarcos, Noemí; Gutierrez, Mario; Liras, Marta; Sánchez, Félix; Douhal, Abderrazzak
<x xml:space="preserve">Abstract</x> Stepwise and coupled photoinduced ICT and ESIPT reactions in a simple derivative of HBO in solution.